2007
DOI: 10.1029/2006gl029130
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of eddy kinetic energy of the North Pacific Subtropical Countercurrent simulated by an eddy‐resolving OGCM

Abstract: [1] The seasonal variation of eddy kinetic energy (EKE) of the North Pacific Subtropical Countercurrent (STCC) was investigated by analyzing the data from an eddy-resolving OGCM with the horizontal resolution 1/12°in comparison with satellite altimetry data. Although the annual cycle of simulated EKE of the whole STCC domain showed agreement with satellite data, with a maximum in spring and a minimum in fall, it revealed latitudinal dependence; that is, near 19°N the EKE level is higher in summer than in winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Also, the large increase in EKE in the FWD experiment, after the change to WRF forcing, is not seen in assimilation experiments, as EKE values maintain a range of 200-300 (cm/s) 2 over the domain and 400-700 (cm/s) 2 in lee during this time period. The EKE levels from assimilation experiments agree well with estimates from eddy-resolving ocean general circulation models [Noh et al, 2007].…”
Section: Impact Of Assimilation On Low-frequency Dynamicssupporting
confidence: 73%
“…Also, the large increase in EKE in the FWD experiment, after the change to WRF forcing, is not seen in assimilation experiments, as EKE values maintain a range of 200-300 (cm/s) 2 over the domain and 400-700 (cm/s) 2 in lee during this time period. The EKE levels from assimilation experiments agree well with estimates from eddy-resolving ocean general circulation models [Noh et al, 2007].…”
Section: Impact Of Assimilation On Low-frequency Dynamicssupporting
confidence: 73%
“…The fact that this second enhanced eddy variability band is associated with the North Pacific Subtropical Countercurrent (STCC) has been noted by several recent studies (e.g., Qiu 1999;Roemmich and Gilson 2001;Kobashi and Kawamura 2002;Noh et al 2007). Figure 2 shows the typical latitude-depth section of time-mean temperature and zonal geostrophic velocity in the western North Pacific Ocean.…”
Section: Introductionmentioning
confidence: 86%
“…Although the NEC is very stable, the vertically sheared NEC‐STCC is baroclinically unstable, this process being more important than its interaction with the Subtropical Front in terms of eddy field generation and seasonal modulation [ Qiu , 1999]. Consequently, its variability generates the second highest eddy kinetic energy regions of the north Pacific [see Qiu , 1999; Noh et al , 2007]. However, the latter studies did not analyze the narrow multiple mean circulation bands of the STCC demonstrated by Hasunuma and Yoshida [1978], who found three separated eastward flows near 19°N, 23°N, and 28°N west of 140°E.…”
Section: North Pacific Ocean Circulationmentioning
confidence: 99%